2019
DOI: 10.5114/pedm.2019.89642
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant parathyroid hormone for hypoparathyroidism in children: a narrative review

Abstract: The conventional management of hypoparathyroidism in children involves the use of calcium and vitamin D analogs. This therapy effectively increases the serum calcium levels but worsens hypercalciuria and its consequences such as nephrocalcinosis and renal insufficiency. Although replacement with the missing parathyroid hormone (PTH) is ideal and available for more than 2 decades, the reported concerns of osteosarcoma prohibited its use in children with open epiphyses. Nevertheless, the data accumulated over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
(74 reference statements)
2
8
0
Order By: Relevance
“…Several recent studies have reported experience with rhPTH1 -34 and recommend the use of rhPTH1 -34 in adults as well as children for management of chronic HPT [10][11][12][13][14]. A recent review that included short and long-term experience on the use of rhPTH1 -34 in 70 children suggested rhPTH1 -34 to be an effective therapy for HPT that improves metabolic control and quality of life and is associated with better renal outcome in children with HPT [5]. Other reassuring features in our patient were a normal BMD after 10 years of PTH therapy, probably indicating a normal trajectory of bone accrual, and the attainment of height within the genetic potential.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several recent studies have reported experience with rhPTH1 -34 and recommend the use of rhPTH1 -34 in adults as well as children for management of chronic HPT [10][11][12][13][14]. A recent review that included short and long-term experience on the use of rhPTH1 -34 in 70 children suggested rhPTH1 -34 to be an effective therapy for HPT that improves metabolic control and quality of life and is associated with better renal outcome in children with HPT [5]. Other reassuring features in our patient were a normal BMD after 10 years of PTH therapy, probably indicating a normal trajectory of bone accrual, and the attainment of height within the genetic potential.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rhPTH1 -34 is prohibited in children with open epiphyses due to concerns of osteosarcoma reported in animal studies that led to black box warning Table I. by the FDA [5]. We monitored bone turnover by estimation of serum ALP at each clinic visit in addition to specific enquiries about any bone-related symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations